Memory Histories, Theories, Debates - Radstone, Susannah; Schwarz, Bill (Fordham University Press, 2010)
The volume reconstructs the work of the great philosophical and literary figures of the last two centuries who recast the concept of memory and brought it into the forefront of the modernist and postmodernist imagination-among them, Bergson, Halbwachs, Freud, Proust, Benjamin, Adorno, Derrida, and Deleuze. Drawing on recent advances in the sciences and in the humanities, the contributors address the question of how memory works, highlighting transactions between the interiority of subjective memory and the larger fields of public or collective memory.